Multi-national survey on the methods, efficacy, and safety on the post-approval clinical use of pulsed field ablation (MANIFEST-PF) . Issue 8 (1st June 2022) - Ekanem, Emmanuel; Reddy, Vivek Y; Schmidt, Boris; Reichlin, Tobias; Neven, Kars; Metzner, Andreas; Hansen, Jim; Blaauw, Yuri; Maury, Philippe; Arentz, Thomas; Sommer, Philipp; Anic, Ante; et al.
Abstract: Aims: Pulsed field ablation (PFA) is a novel atrial fibrillation (AF) ablation modality that has demonstrated preferential tissue ablation, including no oesophageal damage, in first-in-human clinical trials. In the MANIFEST-PF survey, we investigated the 'real world' performance of the only approved PFA catheter, including acute effectiveness and safety—in particular, rare oesophageal effects and other unforeseen PFA-related complications. Methods and results: This retrospective survey included all 24 clinical centres using the pentaspline PFA catheter after regulatory approval. Institution-level data were obtained on patient characteristics, procedure parameters, acute efficacy, and adverse events. With an average of 73 patients treated per centre (range 7–291), full cohort included 1758 patients: mean age 61.6 years (range 19–92), female 34%, first-time ablation 94%, paroxysmal/persistent AF 58/35%. Most procedures employed deep sedation without intubation (82.1%), and 15.1% were discharged same day. Pulmonary vein isolation (PVI) was successful in 99.9% (range 98.9–100%). Procedure time was 65 min (38–215). There were no oesophageal complications or phrenic nerve injuries persisting past hospital discharge. Major complications (1.6%) were pericardial tamponade (0.97%) and stroke (0.4%); one stroke resulted in death (0.06%). Minor complications (3.9%) were primarily vascular (3.3%), but also included transient phrenic nerve paresis (0.46%), and TIA (0.11%). Rare complications included coronary artery spasm, haemoptysis, and dry cough persistent for 6 weeks (0.06% each). Conclusion: In a large cohort of unselected patients, PFA was efficacious for PVI, and expressed a safety profile consistent with preferential tissue ablation. However, the frequency of 'generic' catheter complications (tamponade, stroke) underscores the need for improvement. Graphical Abstract: Graphical Abstract